Japanese National Identity in Light of Kokutai's Theory (1825-1945) - al-Zubaidi, Riyam Ahmed Abed; al-Dulaimi, Waleed Abood Mohammed (Journal of Ecohumanism, 2024)
This research attempts to trace the roots of Japan's national identity in its political concept, nature, growth and evolution through historiography, and the extent to which it is influenced by internal and external political developments, given the emergence of some intellectual schools that advocated the principle of Japanese ethnic superiority. In this regard, the visions of Sechesai Aizawa, the thinker and teacher of the Mitugaku National School, and its most prominent advocates have emerged. When in 1825 he introduced the Kokutai theory, which formed the basic building block of Japan's libertarian thought, She called for the sanctity of the Japanese Earth, the Emperor's reverence and loyalty to him and the need to restore his divinity and role in governance. and alerted to the seriousness of the Western threat and Christian proselytization, committing politicians to liberating Japanese land and will from foreign penetration into Japan as a national and religious duty. These ultranationalist foundations and sentiments, based on the concept of "nation, state and family in the system of their societal traditions", have been restored as the sacred book of nationalists and the philosophical and theoretical basis of the national movement and modern and contemporary Japanese political thought. In the same context, research focused on the extent to which these ideas are reflected and elaborated in different State institutions and, in particular, the military and educational institutions that played an important role in assuming responsibility for restoring Japan's security and embodying its political nationalist identity as a sacred nation protected by the gods and unique and distinct in everything, This was reflected in its expansionist tendency to establish its existence as a powerful State at the regional and international levels. The outbreak of the First World War in 1914 was an occasion to justify its expansionist policy and turn it into an economic and imperialist force influencing the international level. What has come with time in the face of contradicting her visions and objectives with the West that is hostile to her aspirations on the one hand, Japan ' and its move to extreme right-wing national trends that led Japan to a policy of expansion and alliance with totalitarian States, and hence its involvement in the Second World War.